Unravelling supramolecular features and opto-electronic properties of a binary charge transfer cocrystal of a blue fluorescent di-carbazole and TFT. Issue 38 (8th September 2022) - Mandal, Arkalekha; Nath, Bhaskar
Abstract : Strong emission in a mixed stack charge transfer cocrystal comprising a bis-carbazole donor and TFT acceptor is elucidated by crystallographic, fluorescence and electronic property studies. Abstract : Co-assembled crystalline organic systems demonstrate advanced opto-electronic properties by maintaining high molecular order in the crystal packing through non-covalent interactions. In this contribution, a 1 : 2 donor acceptor charge transfer cocrystal with a mixed π-stack (⋯DADADA⋯) arrangement, comprising a blue fluorescent bis-carbazole CBP (4, 4′-bis(9 H -carbazole-9-yl)biphenyl) as the donor chromophore (D) and TFT (tetrafluoroterephthalonitrile) as the acceptor coformer (A), is explored by crystallographic, spectroscopic and electronic property studies. Energy framework and energy decomposition analyses show that the main component of the π⋯π stacking interaction is dispersive force. This cocrystal shows nearly pure, strong (PLQY = 0.3) and long lived ( τ = 85 ns) green emission originating from charge transfer S0 → S1 transition. Theoretical calculations show that the CBP:(TFT)2 cocrystal is expected to display weakly ambipolar and predominantly n-type semiconductor behaviour. This cocrystal is promising as an active optical waveguide due to its pure green emission with high quantum yield and long fluorescence lifetime, a suitable electronic bandgap of ≈2.45 eV and infinite π⋯π stacking leading to one-dimensional crystal growth.